(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article explains what a healthy lifestyle should actually be like, what laws parents should follow to make their children grow up healthy and fit and stay active in classes, and what aspects should not be overlooked. In addition, in the performance of this responsible task, we have been covered in detail about how educators should behave, in what way they can help parents, through what techniques to instill in the minds of young educators the ability to lead a healthy lifestyle, and the relevant conclusions are presented.